PEDAGOGICAL CONDITIONS OF FORMATION OF MUSICAL INTERESTS OF JUNIOR SCHOOLCHILDREN IN MUSIC LESSONS (Pedagogy of Higher and Secondary Education, 2010)
The article deals with the pedagogical conditions that contribute to the successful formation of musical interests of junior schoolchildren in music lessons.
Keywords: pedagogical conditions; musical interests; musical development; musical skills; artistic and pedagogical communication